Origin and fluxes of atmospheric REE entering an ombrotrophic peat bog in Black Forest (SW Germany): evidence from snow, lichens and mosses - Aubert, Dominique; Le Roux, Gaël; Krachler, Michael; Cheburkin, Andriy K.; Kober, Bernd; Shotyk, William; Stille, Peter (Geochimica et cosmochimica acta, 2006)
The fate of the Rare Earth Elements (REE) were investigated in different types of archives of atmospheric deposition in the Black Forest, Southern Germany: (1) a 70cm snow pack collected on the domed part of a raised bog and representing 2 months of snow accumulation, (2) a snow sample collected close to the road about 500m from the peat bog, (3) two species of lichens and (4) a peat profile representing 400 years of peat accumulation as well as a “preanthropogenic” sample and the living moss layer from the top of the core. REE concentrations in peat are significantly correlated to Ti which is a lithogenic conservative element suggesting that REE are immobile in peat bog environments. Snow, lichens and peat samples show similar PAAS (Post Archean Australian Shale) normalized REE distributions suggesting that the complete atmospheric REE signal is preserved in the peat profile. However, the annual flux of REE accumulated by the peat is ca. 10 times greater than that of the bulk winter flux of REE. This difference probably indicates that the REE concentrations in the snowpack are not representative of the average REE flux over the whole year. Despite the pronounced geological differences between this site (granite host-rock) and a previously studied peat bog in Switzerland (limestone host-rock) similar REE distribution patterns and accumulation rates were found at both sites. Given that both sites confirm an Upper Continental Crust signature, the data suggests both sites are influenced by regional and not local, soil-derived lithogenic aerosols.